(untitled) (Fiep Bulletin - online, 2014)
The aim of this research is to identify the necessary conditions for the development of the American football in Brazil. We investigate here the case of the American football that is practiced at the beaches of Rio de Janeiro and its difficulties in adapting and expanding in the Brazilian sporting culture. We delineate this research from interviews carried through with athletes, managers and sporting journalists who are directly connected to this modality known as Beach Football. We also identify how the sporting media has been treating this modality. Studies in this area contribute to reveal how sports are adapted by the individuals and by the culture in which they are inserted, even when they are practiced in a distinct way from their native countries.